Melting of 3 He in a phase-separated solid 3He - 4He mixture - Haley, R. P.; Adams, E. D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The melting pressure of the 3He-rich phase, formed after phase separation of a mixture of 0.6% 3He in 4He, has been studied in the temperature range 1-150 mK, below the phase-separation temperature Tps, at pressures between 2.78 and 3.56 MPa. Measurements were made with the mixture confined in a silver sinter, and also in an open volume for comparison. An elevation of the melting pressure relative to pure 3He of up to 60 kPa in the sinter cell and 20 kPa in the open-volume cell was observed. Hysteresis between the freezing and melting temperatures was found for both cells, similar to that observed for pure 3He in small pores. The results of Schrenk et al. for heat capacity measurements on a similar system are discussed.